Latent myopathy is more pronounced in patients with low flow versus normal flow aortic stenosis with normal left ventricular ejection fraction who are undergoing surgical aortic valve replacement: Multicenter study with a brief review of the literature. Issue 5 (1st April 2018) - Supariwala, Azhar; Sanchez‐Ross, Monica; Suma, Valentin; Seetharam, Karthik; Marrero, Daniel; Swistel, Daniel; Balaram, Sandhya; Chaudhry, Farooq A.
Abstract : Background: Midwall fibrosis and low stroke volume are independent predictors of mortality in severe aortic stenosis (AS) with preserved LV ejection fraction (LVEF). The role of speckle tracking echocardiography (STE) to identify latent myopathy pre‐ and post‐ aortic valve replacement (AVR) in high risk AS patients with normal LVEF is limited. Methods: Demographic, 2D echocardiographic, and STE data were analyzed in patients with severe AS and preserved LVEF who underwent tissue AVR. Velocity vector imaging (VVI) was used to assess regional and global peak systolic longitudinal strain (GLS). Low flow (LF) was defined as an indexed LV stroke volume <35 mL/m 2 . Results: Between December 2008 and May 2011, 37 patients (75 ± 9 years, 51% male) had both pre‐ and post‐AVR echos within 6.6 ± 6.5 months (median = 4 months; range = 2.5–9.5) of surgery. Compared with pre‐AVR, GLS (−6.9 ± 4.9% vs −11.1 ± 4.1%; P  < .001) and strain rate (−0.72 ± 0.3s ‐1 vs −0.87 ± 0.3s ‐1 ; P  = .01) improved post‐AVR. Pre‐AVR mid‐segments showed a similar myopathy as the basal segments (−9.5 ± 4.3% vs −9.0 ± 4.2%; P  = .3). The 16 (43%) LF patients in this study had lower pre‐ and post‐AVR strain compared to NF patients (GLS Pre‐AVR:LF vs NF: −5.1 ± 4.1% vs −8.4 ± 4.9% ( P  = .04) and GLS Post‐AVR:LF vs NF: −9.2 ± 3.7% vs −12.5 ± 3.9% ( P  = .01)). However, there was no difference in absolute and %change improvement in GLS post‐AVR (LF vs NF:∆ −4.2 ± 3.5% vs ∆−4.1 ± 5.3% ( P  = .90) and 193 ± 214% vs 143 ± 230% change ( P  = .5)). The lowest GLS was seen in LF/HG AS followed by LF/LG, NF/LG and NF/HG AS; P  = .03. Conclusions: Latent myopathy is more pronounced in LF AS both pre‐ and post‐AVR. Our study provides evidence of improvement in myopathy in LF AS despite a persistent worse myopathy compared to NF patients post‐AVR.